Diagnosis and management of a giant ovarian cyst during pregnancy and puerperium: Case series (Panacea Journal of Medical Sciences, 2022)
Background: In the pregnancy and puerperium phase, giant ovarian cysts are highly uncommon. It raises the risk of fetal and maternal morbidity. We describe three cases of large benign ovarian cysts diagnosed and treated at a rural medical college and hospital with limited facilities during the pregnancy and puerperium phase.Case Presentation: Data were obtained by history analysis, clinical assessment, laboratory examination, radiological imaging, and histopathological analysis of the culled surgical specimen. Our first case was a 23-year-old primigravida who presented with pain in abdomen. Antenatal sonography confirmed a huge intact left ovarian cyst. She was managed at term by cesarean for obstetrical indication along with left ovarian cystectomy. Our second case, a 25-year-old woman, reported abdominal distention following uncomplicated vaginal delivery. After a complete workup, she was diagnosed with a benign serous ovarian cystadenoma. Laparotomy with left ovarian cystectomy was done. In our third scenario, a 20-year-old primigravida with a giant ovarian cyst at 34 weeks gestation who also delivered vaginally and underwent laparotomy with left ovarian cystectomy. Histopathological examination revealed benign ovarian serous adenoma in all three cases.Conclusion: When a large ovarian cyst is present during pregnancy, it is unearthed that vaginal delivery is possible. In the postpartum period, surgical cyst treatment can be performed with satisfaction.